Advocacy Coalition Constellations and Norm Collisions: Insights from International Drug Control, Human Trafficking, and Child Labour - Anna Holzscheiter; Sassan Gholiagha; Andrea Liese (Global Society, 2022)
To date, there has been little research on how advocacy coalitions influence the dynamic relationships between norms. Addressing norm collisions as a particular type of norm dynamics, we ask if and how advocacy coalitions and the constellations between them bring such norm collisions to the fore. Norm collisions surface in situations in which actors claim that two or more norms are incompatible with each other, promoting different, even opposing, behavioural choices. We examine the effect of advocacy coalition constellations (ACC) on the activation and varying evolution of norm collisions in three issue areas: international drug control, human trafficking, and child labour. These areas have a legally codified prohibitive regime in common. At the same time, they differ with regard to the specific ACC present. Exploiting this variation, we generate insights into how power asymmetries and other characteristics of ACC affect norm collisions across our three issue areas.
Keywords: 300; norm collisions; advocacy coalitions; drug control; human trafficking; child labour; norms